2021
DOI: 10.3389/fnhum.2021.748241
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effects of Intermittent Theta Burst Stimulation of the Cerebellar Vermis on Cerebral Cortical Excitability During a Balance Task in Healthy Individuals: A Pilot Study

Abstract: Objective: This pilot study aimed to investigate the immediate effects of single-session intermittent theta-burst stimulation (iTBS) on the cerebellar vermis during a balance task, which could unveil the changes of cerebral cortical excitability in healthy individuals.Subjects: A total of seven right-handed healthy subjects (26.86 ± 5.30 years) were included in this study.Interventions: Each subject received single-session iTBS on cerebellar vermis in a sitting position.Main Measures: Before and after the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In the block-design balance tasks measured by fNIRS, a major activation trend (P > 0.05 FDR-corrected) was observed on ipsilateral DLPFC, PM-SMC, and contralateral PMC after CB-SMA iTBS protocol in the EC balance block-designed fNIRS task. The activation of bilateral SMA after single-CB iTBS has been observed when healthy people perform balance tasks ( 22 ). Meanwhile, the activation of the DLPFC may represent a compensation effect for demanding balance tasks when patients have sensorimotor deficits ( 24 ), as well as a representation of better neural efficiency ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the block-design balance tasks measured by fNIRS, a major activation trend (P > 0.05 FDR-corrected) was observed on ipsilateral DLPFC, PM-SMC, and contralateral PMC after CB-SMA iTBS protocol in the EC balance block-designed fNIRS task. The activation of bilateral SMA after single-CB iTBS has been observed when healthy people perform balance tasks ( 22 ). Meanwhile, the activation of the DLPFC may represent a compensation effect for demanding balance tasks when patients have sensorimotor deficits ( 24 ), as well as a representation of better neural efficiency ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…1, 4), Broca's network (Ch. 15,21,22), Wernicke network (Ch. 2, 3, 5, 7, 8, 10, 11), sensory network (Ch.…”
Section: Whole-brain Fc Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary pilot study found that cerebellar vermis iTBS contributed to increasing the excitability of the bilateral supplementary motor areas (SMAs) during balance tasks in healthy adults. 23 …”
Section: Introductionmentioning
confidence: 99%
“…During the whole stepping process, proper engagement of the cortical cortex is also crucial to the balance equilibrium. The regions of the prefrontal cortex (PFC), pre-motor cortex (PMC), and primary motor cortex (M1) are all believed to participate in the regulation of balance control [ 14 ]. The reduced connectivity between cortical regions in older adults is accompanied by a worse performance of balance scales [ 15 ].…”
Section: Introductionmentioning
confidence: 99%